IMPROVING LEARNING OUTCOMES FOR OUT-OF-SCHOOL CHILDREN: EVIDENCE FROM A RANDOMIZED EVALUATION OF AN ACCELERATED LEARNING PROGRAM IN LIBERIA. (Лучшие интеллектуальные исследования, 2025)
Annotation: Children in Liberia receive 2.2 learning-adjusted years of schooling, one of the lowest levels of educational attainment in the world. We study one approach to address low enrollment and low rates of learning: a 10-month accelerated learning program run by the Luminos Fund to help out-of-school children catch up to grade level. We conducted a randomized evaluation of the program across 100 communities in Liberia. We find that the program had large effects on reading and numeracy skills for out-of-school children, and that children in the program catch up to the learning levels of children in government schools.